2003
DOI: 10.1191/0267659103pf680oa
|View full text |Cite
|
Sign up to set email alerts
|

Departmental use of perfusion crisis management drills: 2002 survey results

Abstract: Serious complications during the performance of cardiopulmonary bypass (CPB) are an infrequent event. However, when potentially fatal technical complications, such as oxygenator or pump failure, do occur, it necessitates a swift and well-co-ordinated response. Periodic performances of drills that simulate various CPB crises are a way to improve individual perfusionist proficiency during disaster situations. The purpose of this study is to determine the utilization of crisis management drills in perfusion depar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 12 publications
0
13
0
Order By: Relevance
“…252,257 Virtually 100% of perfusionists surveyed in 2002 believed that such practice would be beneficial, but only 17% reported that such drills occur. 258 In a recent study of education of whole cardiac surgery teams in crisis management using high-fidelity simulation, participants reported 2 areas of highest priority and improvement: encouraging outspokenness about critical information and improved interprofessional communication by clearly defining the intended recipient (using the name of the person to whom communication is directed) and by attention to "closing the loop" in verbal communications. 259…”
Section: Simulationmentioning
confidence: 99%
“…252,257 Virtually 100% of perfusionists surveyed in 2002 believed that such practice would be beneficial, but only 17% reported that such drills occur. 258 In a recent study of education of whole cardiac surgery teams in crisis management using high-fidelity simulation, participants reported 2 areas of highest priority and improvement: encouraging outspokenness about critical information and improved interprofessional communication by clearly defining the intended recipient (using the name of the person to whom communication is directed) and by attention to "closing the loop" in verbal communications. 259…”
Section: Simulationmentioning
confidence: 99%
“…A Japanese research group showed in several studies [8][9][10] that by practising on a simulator, subjects were able to maintain patient values (blood flow rate and reservoir level) closer to a predetermined level than without practise. Ginther et al 11 tested simulation training in the context of critical situations. In a study with their own students, they showed that mentally going through a sequence of actions (exchanging the oxygenator) before putting it into practise resulted in a 20% faster execution than none at all.…”
Section: Discussionmentioning
confidence: 99%
“…Simulators have also become popular at perfusion meetings for staging drills to practice oxygenator change-out or other CPB emergencies.While perfusion simulators are intriguing and their use is gaining popularity, any perfusion team can perform drills using existing CPB equipment. However, while respondents to a survey 85 indicated the widespread belief that practice and crisis management drills were appropriate, only 17% reported their team members actually performed drills as a matter of departmental policy. Such findings were reconfirmed recently by Darling and Searles.…”
Section: Newer Initiatives Contributing To Perfusion Safetymentioning
confidence: 99%